Lithium-rich manganese-based positive electrode material containing coating layer and application of lithium-rich manganese-based positive electrode material in all-solid-state lithium battery

By covering specific elemental elements and alkali metal compounds on the surface of the lithium-rich manganese-based positive electrode material, the oxygen release and structural degradation of the lithium-rich manganese-based positive electrode material in solid-state lithium-ion batteries is solved, and the cycle stability and rate performance of the battery are improved.

CN119864405APending Publication Date: 2025-04-22ZHEJIANG UNIV OF TECH

Patent Information

Application Number
CN202510093162.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the problems of oxygen release and structural degradation of lithium-rich manganese-based positive electrode materials in solid-state lithium-ion batteries, resulting in deterioration of battery performance.

Method used

By covering elemental elements such as P, As, Te, I and other alkali metal compounds on the surface of the lithium-rich manganese-based positive electrode material, the highly reactive lattice oxygen is captured by surface adsorption or chemical bonding, and the side reaction between the lithium-rich manganese-based positive electrode material and the halide solid electrolyte is reduced.

Benefits of technology

Effectively stabilize the surface of lithium-rich positive electrode, inhibit the release of lattice oxygen, improve the cycle stability and rate performance of lithium-rich manganese-based positive electrode materials, and extend the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864405A_ABST
    Figure CN119864405A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion battery positive electrode materials, and discloses a lithium-rich manganese-based positive electrode material containing a coating layer and application of the lithium-rich manganese-based positive electrode material in an all-solid-state lithium battery. The surface of the lithium-rich manganese-based positive electrode material is coated with at least one of simple substances such as P, As, Te, I and the like and corresponding alkali metal compounds, so that contact between a solid electrolyte and the lithium-rich manganese-based positive electrode material is reduced physically, lattice oxygen is captured in a surface adsorption or chemical combination manner, the surface of the lithium-rich positive electrode is stabilized, and the lithium-rich positive electrode material is more stable in performance. The release of lattice oxygen is inhibited; and meanwhile, the lithium-rich manganese-based positive electrode material containing the coating layer and the high-voltage-resistant halide solid electrolyte are prepared into the composite positive electrode, so that the side reaction between the lithium-rich manganese-based positive electrode material and the solid electrolyte can be reduced, and the improvement of the structural stability of the lithium-rich manganese-based positive electrode material in the circulating process is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of cathode materials for lithium-ion batteries, and particularly relates to a lithium-rich manganese-based cathode material with a coating layer and its application in all-solid-state lithium batteries. Background Art

[0002] In recent years, all-solid-state batteries (ASSBs) have attracted extensive attention due to their excellent safety and high theoretical energy density. All-solid-state batteries use non-flammable inorganic solid electrolytes. Among them, halide solid electrolytes with higher oxidation potentials can reduce the interfacial reaction between high-voltage cathodes and solid electrolytes, making the battery performance more stable.

[0003] Compared with conventional cathode materials such as lithium cobaltate, lithium iron phosphate, and Ni-rich materials, lithium-rich manganese-based cathodes have higher capacities (exceeding 250 mAh / g) and energy densities (about 1000 Wh / kg), and are rich in resources and low in cost. Therefore, they have broad application prospects in all-solid-state batteries.

[0004] However, so far, there has been little research on the application of lithium-rich manganese-based cathodes in solid-state lithium-ion batteries. Sulfide solid electrolytes, as relatively mature solid electrolytes, have high lithium-ion conductivity, but their electrochemical windows are narrow and their oxidation resistance stability is poor. The working voltage range of lithium-rich manganese-based cathodes is between 2.0 V and 4.8 V. At high working voltages, the lithium-rich manganese-based cathode will release highly active lattice oxygen O (2-n)- (0 < n < 2). These highly active lattice oxygen will react with sulfide solid electrolytes to form by-products, increasing the interfacial impedance and hindering the transport of lithium ions. And due to irreversible lattice oxygen loss, the lithium-rich manganese-based cathode will undergo a phase change from layered to spinel, resulting in a sharp deterioration of the performance of sulfide all-solid-state batteries. Halide solid electrolytes have received great attention in the development of lithium-rich manganese-based solid-state batteries due to their superior oxidation stability.

[0005] Based on the liquid battery system, some researchers have deposited sulfur单质 on the surface of lithium-rich manganese-based cathodes to form a bond through charge transfer between S and O. The oxygen released after the lithium-rich manganese-based cathode is de-lithiated can form SO4 with sulfur. 2-, effectively stabilizing the oxygen on the surface of the lithium-rich manganese-based positive electrode, achieving superior electrochemical performance. Recently, researchers (H. Pan et al, A Redox Couple Strategy Enables Long-Cycling Li-and Mn-Rich Layered Oxide Cathodes by Suppressing Oxygen Release. Adv. Mater. 2022, 34, 2108543.) proposed a chalcogenide-coated lithium-rich manganese-based positive electrode material that can regulate the redox of oxygen ions. Alkali metal selenides or alkali metal tellurides are used as coated lithium-rich manganese-based positive electrode materials. Se 2- / SeO3 2- or Te 2- / TeO3 2- As a redox couple, it greatly inhibits the release of oxygen from the lithium-manganese-rich positive electrode during the electrochemical cycle, realizes oxygen ion redox regulation, and improves the cycle stability of the positive electrode.

[0006] However, current research applies a large number of surface modification strategies that have been significantly developed in liquid battery systems to solid-state battery systems. These strategies tend to inhibit the already slow lithium-rich manganese-based cathode transport kinetics and are therefore not suitable for solid-state battery systems. Researchers (Zhou, H et al, Self-constructing a lattice-oxygen-stabilized interface in Li-rich cathodes to enable high-energy all-solid-state batteries. Energy & Environmental Science 2024, 17 (9), 3052-3059.) use single crystal Li2RuO3 as a lithium-rich oxide cathode directly matched with halide solid electrolysis (Li3InCl6), and the prepared solid-state battery has excellent cycle stability and ultra-high energy density, but the expensive price of Ru element limits its development.

[0007] Sun et al. (X.Sun et al, Manipulating Charge-Transfer Kinetics of Lithium-Rich Layered Oxide Cathodes in Halide All-Solid-State Batteries. Adv. Mater. 2023, 35, 2207234.) coated Li3PO4 on the surface of lithium-rich manganese-based positive cathode material by atomic layer deposition (ALD) technology, which effectively inhibited the oxidation of solid electrolyte Li3InCl6 and the structural degradation of lithium-rich manganese-based positive electrode. However, atomic layer deposition technology is only suitable for small-scale laboratory experiments, with high cost and low preparation efficiency.

[0008] Therefore, how to modify the surface of lithium-rich manganese-based positive electrode materials and enable them to be effectively used in solid-state batteries is still a problem that needs to be further solved in the field. Summary of the invention

[0009] In order to solve the above-mentioned technical problems, the present invention provides a lithium-rich manganese-based positive electrode material containing a coating layer and its application in an all-solid-state lithium battery.

[0010] The present invention prepares a solid-state battery electrode from a lithium-rich manganese-based positive electrode material and a halide solid electrolyte, which can reduce the degree of deterioration between the contact interface between the lithium-rich manganese-based positive electrode material and the solid electrolyte (compared to the interface between the lithium-rich manganese-based positive electrode material and the sulfide solid electrolyte). By modifying the surface coating layer, the side reaction between the lithium-rich manganese-based positive electrode material and the halide solid electrolyte is further reduced, which helps to improve the structural stability of the lithium-rich manganese-based positive electrode material during the cycle process.

[0011] The technical solution adopted by the present invention to achieve the above technical purpose is as follows:

[0012] The present invention provides a lithium-rich manganese-based positive electrode material containing a coating layer, wherein the coating of the coating layer is selected from at least one of the elemental simple substance of P, As, Te, I and the corresponding alkali metal compound thereof, and the alkali metal includes at least one of Li, Na and K. By adopting the technical solution, while physically reducing the contact between the solid electrolyte and the lithium-rich manganese-based positive electrode material, the lattice oxygen released by the lithium-rich manganese positive electrode under high voltage can be captured in situ by surface adsorption or chemical bonding, so as to stabilize the surface of the lithium-rich positive electrode and inhibit the release of lattice oxygen.

[0013] Preferably, the coating layer is at least one of P, As, Te, I, Na3P, K3P, Na3As, LiI, KI, and NaI.

[0014] Preferably, the chemical formula of the lithium-rich manganese-based positive electrode material is xLi2MnO3·(1-x)LiMO2; wherein M is at least one of Mn, Co, and Ni; 0≤x≤1.

[0015] Preferably, the weight of the coating layer is 0.01 to 20%, more preferably 1 to 6%, of the lithium-rich manganese-based positive electrode material containing the coating layer.

[0016] Preferably, the coating layer is coated on the surface of the lithium-rich manganese-based positive electrode material by a coating method; the coating method is selected from at least one of a liquid phase coating method, a solid phase coating method and a gas phase coating method; more preferably, the liquid phase coating method; including but not limited to a hydrothermal method, a precipitation method, a sol-gel method, a chemical plating method, etc.; the solid phase coating method: including but not limited to a mechanical mixing method, a solid phase reaction method, etc.; the gas phase coating method: including but not limited to a physical vapor deposition method, a chemical vapor deposition method, an atomic layer deposition method, etc.

[0017] The present invention also provides a use of any of the above-mentioned lithium-rich manganese-based positive electrode materials containing a coating layer in an all-solid-state lithium battery.

[0018] Preferably, the application includes an all-solid-state lithium battery, the all-solid-state lithium battery includes a solid electrolyte, and the solid electrolyte includes a halide solid electrolyte; more preferably, the chemical formula of the halide solid electrolyte is Li a MX b , wherein M is one or more of Al, Ga, In, Sc, Y, and La, X is one or more of F, Cl, and Br, 0≤a≤10, 1≤b≤13. More preferably, the halide solid electrolyte includes, but is not limited to, one or more of Li3InCl6, Li3YCl6, Li3YBr6, Li3HoCl6, and Li3ScCl6.

[0019] Preferably, the all-solid-state lithium battery comprises a composite lithium-rich manganese positive electrode material, which is obtained by fully mixing and grinding any one of the above-mentioned lithium-rich manganese-based positive electrode materials containing a coating layer, a halide solid electrolyte powder and a conductive agent; more preferably, the mass ratio of the lithium-rich manganese-based positive electrode material containing a coating layer, the halide solid electrolyte and the conductive agent is 30-90:20-45:3-7.

[0020] Furthermore, the conductive agent is one or a mixture of two or more of carbon black, carbon nanotubes, acetylene black, VGCF, SuperP, conductive graphite, and carbon fiber.

[0021] Furthermore, the halide solid electrolyte can be uniformly mixed with the lithium-rich manganese-based positive electrode material containing the coating layer by mechanical stirring, ball milling, ultrasound, etc.

[0022] Furthermore, the weight ratio of the halide solid electrolyte to the lithium-rich manganese-based positive electrode material is (1:99)-(99:1), preferably (10:90)-(30:70).

[0023] Furthermore, the solid electrolyte of the all-solid-state lithium battery includes a halide solid electrolyte layer and a sulfide solid electrolyte layer, the halide solid electrolyte layer is laminated with the composite lithium-rich manganese positive electrode material, and the sulfide solid electrolyte layer is laminated with the negative electrode material. More preferably, the thickness ratio of the sulfide solid electrolyte layer to the halide solid electrolyte layer is 1:2; more preferably, the thickness of the solid electrolyte layer is 600μm.

[0024] Furthermore, the sulfide solid electrolyte of the sulfide solid electrolyte layer includes one or more of a LISICON-type sulfide solid electrolyte, an argyrodite-type solid electrolyte, and an LGPS-type sulfide solid electrolyte.

[0025] Further, the negative electrode material is one or a mixture of two or more of lithium metal, lithium-containing alloy, graphite, hard carbon, silicon carbon, lithium titanate, etc. More preferably, the lithium-containing alloy is selected from at least one of lithium-indium alloy, lithium-silver alloy, lithium-aluminum alloy, lithium-tin alloy, etc.

[0026] Preferably, the method for preparing the all-solid-state lithium battery comprises the following steps:

[0027] 1) fully mixing and grinding the lithium-rich manganese-based positive electrode material, the halide solid electrolyte powder and the conductive agent in a mass ratio of 30-90:20-45:3-7 to obtain a composite lithium-rich manganese positive electrode material;

[0028] 2) sequentially and uniformly sprinkle the halide solid electrolyte powder and the sulfide solid electrolyte powder into a tablet pressing mold, and maintain the pressure at 300-500 MPa for 30s-60s to press the powder electrolyte into tablets; obtaining a double-layer heterogeneous electrolyte layer containing a sulfide solid electrolyte layer and a halide solid electrolyte layer disposed adjacently; more preferably, 50 mg of sulfide solid electrolyte powder and 80 mg of halide solid electrolyte powder; the total thickness of the solid electrolyte layer is 600 μm;

[0029] 3) Sprinkling the composite lithium-rich manganese positive electrode material evenly on the halide solid electrolyte side of the solid electrolyte sheet, and maintaining the pressure at a pressure of 300 to 500 MPa for 60 to 120 seconds; more preferably, the composite lithium-rich manganese positive electrode material is 8 mg, and the thickness after pressing is preferably 70 μm;

[0030] 4) Add negative electrode material to the sulfide solid electrolyte side of the solid electrolyte sheet. More preferably, the negative electrode material is lithium metal, and the thickness after pressing is 30 μm.

[0031] The present invention provides a coating method for lithium-rich manganese and its application in an all-solid-state battery. The coating layer on the surface of the material not only has the advantages of a traditional coating layer: (1) P, As, Te, I elemental simple substances and their alkali metal compounds can reduce the direct contact between the lithium-rich manganese-based positive electrode material and the electrolyte, alleviate the side reaction between the electrode and the solid electrolyte, improve the interface stability, and increase the cycle stability of the lithium-rich manganese-based solid-state battery; and (2) the coating of P, As, Te, I elemental simple substances and their alkali metal compounds can capture the highly active lattice oxygen released in the lithium-rich manganese-based positive electrode material under high voltage by surface adsorption or chemical bonding, avoid the deterioration reaction between the solid electrolyte and the highly active lattice oxygen, and at the same time can improve the cycle stability and rate performance of the solid-state battery, and can effectively inhibit voltage decay.

[0032] Compared with the prior art, the present invention has the following beneficial effects: the present invention coats the surface of the lithium-rich manganese-based positive electrode material with single elements such as P, As, Te, I and their alkali metal compounds, while physically reducing the contact between the solid electrolyte and the lithium-rich manganese-based positive electrode material, and captures lattice oxygen by surface adsorption or chemical bonding to stabilize the surface of the lithium-rich positive electrode and inhibit the release of lattice oxygen; at the same time, the lithium-rich manganese-based positive electrode material and the high-pressure resistant halide solid electrolyte are prepared into a composite positive electrode, which can reduce the side reaction between the lithium-rich manganese-based positive electrode material and the solid electrolyte, and help to improve the structural stability of the lithium-rich manganese-based positive electrode material during the cycle. Therefore, it has broad market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The capacity efficiency curves are obtained by performing charge and discharge tests on solid-state batteries assembled in Example 1 and Comparative Example 1 at 30°C and 0.1C for 100 cycles.

[0034] Figure 2 The capacity efficiency curves are obtained by performing charge and discharge tests on solid-state batteries assembled from Example 2 and Comparative Example 1 at 30°C and 0.1C for 100 cycles.

[0035] Figure 3 The charge and discharge curves of the first cycle of the solid-state battery assembled in Example 3 and Comparative Example 1 under the charge and discharge test at 60°C and 0.1C.

[0036] Figure 4 The capacity efficiency curves are obtained by performing charge and discharge tests on solid-state batteries assembled from Example 4 and Comparative Example 1 at 60°C and 0.5C for 100 cycles.

[0037] Figure 5 The charge and discharge curves obtained by performing the first cycle charge and discharge test of the solid-state battery assembled in Example 5 and Comparative Example 1 at 30°C and 0.1C.

[0038] Figure 6The median voltage curve is obtained by performing a charge and discharge test on the solid-state battery assembled from Example 6 and Comparative Example 1 at 30°C and 0.1C for 100 cycles.

[0039] Figure 7 The capacity efficiency curve is obtained by performing a charge and discharge test of 100 cycles at 30°C and 0.1C on the solid-state battery assembled in Example 7 and Comparative Example 1.

[0040] Figure 8 The impedance values ​​of the solid-state batteries assembled in Example 8 and Comparative Example 1 after the first cycle charge and discharge test at 30°C and 0.1C.

[0041] Fig. 9 DQ / DV curves obtained when the solid-state batteries assembled in Example 9 and Comparative Example 1 were subjected to the first cycle charge and discharge test at 30°C and 0.1C.

[0042] Fig.10 The impedance values ​​of the solid-state batteries assembled in Example 10 and Comparative Example 1 after 100 cycles of charge and discharge testing at 30°C and 0.1C.

[0043] Fig.11 The charge and discharge curves obtained by performing the first cycle charge and discharge test at 30°C and 0.1C for the solid-state battery assembled in Comparative Example 1.

[0044] Fig.12 It is a schematic diagram of the structure of the all-solid-state batteries prepared in Examples 1-10 of the present invention and Comparative Example 1.

[0045] Fig.13 It is a schematic diagram of the strategy of the lithium-rich manganese-based positive electrode material of the present invention. DETAILED DESCRIPTION

[0046] In order to better clarify and understand the purpose, process scheme and advantages of the present invention, the technical scheme and implementation method of the present invention are further described clearly, completely and in detail through specific examples and in combination with the accompanying drawings. It should be noted that the embodiments described in the present invention are implemented on the premise of the technical scheme of the present invention, and detailed implementation methods and specific operating processes are given, but they are only part of the embodiments of the present invention, not all of the embodiments. The specific implementation methods described are limited to explaining and interpreting the present invention, and do not limit the present invention. Based on the embodiments in the present invention, all other implementation methods obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0047] The experimental methods and conditions used in the embodiments of the present invention are conventional methods and conventional conditions unless otherwise specified. The materials, reagents or instruments used in the embodiments, unless otherwise specified, can be obtained from commercial sources or prepared by conventional methods. The reaction conditions embodied in the content of the invention of the present invention can achieve the reaction and obtain the product of the expected effect. Due to space limitations, some embodiments are listed below to further illustrate the advantages of the technical solution of the present invention.

[0048] Embodiment 1:

[0049] A lithium-rich manganese-based positive electrode material containing a coating layer and application thereof in an all-solid-state lithium battery, comprising the following steps:

[0050] (1) Coating the lithium-rich manganese-based positive electrode material by ball milling: First, weigh 1g of lithium-rich manganese-based positive electrode material (Li 1.2 Mn 0.54 Co 0.13 Ni 0.13 O2), 0.03g elemental phosphorus (P), sealed in a ball mill jar under an inert atmosphere, H2O < 0.01ppm, O2 < 0.01ppm in the inert atmosphere, then ball milled in a ball mill at a speed of 400r / min for 2h to obtain a coated lithium-rich manganese-based positive electrode material, and finally transferred to a glove box under an inert atmosphere to obtain a lithium-rich manganese-based positive electrode material coated with elemental phosphorus;

[0051] (2) Weigh 0.65 g of the lithium-rich manganese-based positive electrode particles coated with elemental phosphorus (P) obtained in step 1), 0.30 g of Li3InCl6 halide solid electrolyte and 0.05 g of VGCF in a mortar in a mass ratio of 65:30:5, and grind them in a mortar for 20 min to obtain a composite positive electrode raw material;

[0052] (3) Weigh 80 mg of Li3InCl6 halide solid electrolyte, put it into the inner tank of a solid-state battery mold with a diameter of 12 mm and spread it evenly, and then press it into a tablet at a pressure of 300-500 MPa; continue to weigh 50 mg of Li6PS5Cl sulfide solid electrolyte, put it into the solid-state battery mold where the Li3InCl6 halide solid electrolyte sheet already exists and spread it evenly, and then press it into a double-layer heterogeneous electrolyte layer with the halide solid electrolyte layer at a pressure of 300-500 MPa, and maintain the pressure for 60 seconds;

[0053] (4) Weigh 8 mg of the composite positive electrode raw material obtained in step 2), put it into the inner tank of the solid-state battery mold on one side of the Li3InCl6 halide solid electrolyte and spread it evenly, then compact the composite positive electrode raw material and the double-layer electrolyte layer at a pressure of 300 to 500 MPa, and maintain the pressure for 60 seconds;

[0054] (5) A lithium sheet with a diameter of 10 mm and a thickness of 0.2 mm was attached to one side of the Li6PS5Cl sulfide solid electrolyte and then compacted at a pressure of 10 MPa;

[0055] (6) Finally, the solid-state battery mold liner is placed into the solid-state battery mold, and the screws are tightened at a pressure of 30 MPa for packaging to obtain a lithium-rich manganese-based all-solid-state battery.

[0056] (7) Figure 1 As shown, the all-solid-state battery was subjected to a long cycle charge and discharge test at 30°C and 0.1C. Compared with Comparative Example 1, it can be seen that the capacity and capacity retention rate of the lithium-rich manganese-based positive electrode material coated with elemental phosphorus are significantly improved.

[0057] Embodiment 2:

[0058] A lithium-rich manganese-based positive electrode material containing a coating layer and application thereof in an all-solid-state lithium battery, comprising the following steps:

[0059] (1) Coating the lithium-rich manganese-based positive electrode material by ball milling: First, weigh 1g of lithium-rich manganese-based positive electrode material (Li 1.2 Mn 0.54 Co 0.13 Ni 0.13 O2), 0.03g of elemental arsenic (As), sealed in a ball mill under an inert atmosphere, in which H2O < 0.01ppm, O2 < 0.01ppm, then ball milled in a ball mill at a speed of 300r / min for 4h to obtain a coated lithium-rich manganese-based positive electrode material, and finally transferred to a glove box under an inert atmosphere to obtain a lithium-rich manganese-based positive electrode material coated with elemental arsenic;

[0060] (2) Weigh 0.65 g of the lithium-rich manganese-based positive electrode particles coated with elemental arsenic (As) obtained in step 1), 0.30 g of Li3InCl6 halide solid electrolyte and 0.05 g of VGCF in a mortar in a mass ratio of 65:30:5, and grind them in a mortar for 20 min to obtain a composite positive electrode raw material;

[0061] (3) Weigh 80 mg of Li3InCl6 halide solid electrolyte, put it into the inner tank of a solid-state battery mold with a diameter of 12 mm and spread it evenly, and then press it into a tablet at a pressure of 300-500 MPa; continue to weigh 50 mg of Li6PS5Cl sulfide solid electrolyte, put it into the solid-state battery mold where the Li3InCl6 halide solid electrolyte sheet already exists and spread it evenly, and then press it into a double-layer heterogeneous electrolyte layer with the halide solid electrolyte layer at a pressure of 300-500 MPa, and maintain the pressure for 60 seconds;

[0062] (4) Weigh 23 mg of the composite positive electrode raw material obtained in step 2), put it into the inner tank of the solid-state battery mold on one side of the Li3InCl6 halide solid electrolyte and spread it evenly, then compact the composite positive electrode raw material and the double-layer electrolyte layer at a pressure of 300 to 500 MPa, and maintain the pressure for 60 seconds;

[0063] (5) A lithium sheet with a diameter of 10 mm and a thickness of 0.2 mm was attached to one side of the Li6PS5Cl sulfide solid electrolyte and then compacted at a pressure of 10 MPa;

[0064] (6) Finally, the solid-state battery mold liner is placed into the solid-state battery mold, and the screws are tightened at a pressure of 30 MPa for packaging to obtain a lithium-rich manganese-based all-solid-state battery;

[0065] (7) Figure 2 As shown, the all-solid-state battery was charged and discharged at 30°C, 0.1C, and a large loading of 15 mg (loading of arsenic-coated lithium-manganese-based positive electrode particles). Compared with Comparative Example 1, it can be seen that the capacity and capacity retention rate of the lithium-rich manganese-based positive electrode material coated with elemental arsenic are significantly improved.

[0066] Embodiment 3:

[0067] A lithium-rich manganese-based positive electrode material containing a coating layer and application thereof in an all-solid-state lithium battery, comprising the following steps:

[0068] (1) Coating the lithium-rich manganese-based positive electrode material by melting method: First, weigh 1g of lithium-rich manganese-based positive electrode material (Li 1.2 Mn 0.54 Co 0.13 Ni 0.13 O2), 0.015g of elemental tellurium (Te) was put into a mortar and mixed for 20 minutes, the temperature was raised to 400-500°C at a heating rate of 2-4°C / min, calcined for 4-6 hours in an argon atmosphere, and finally transferred to a glove box under an inert atmosphere to obtain a lithium-rich manganese-based positive electrode material coated with elemental tellurium;

[0069] (2) Weigh 0.65 g of the lithium-rich manganese-based positive electrode particles coated with tellurium (Te) obtained in step 1), 0.30 g of Li3YCl6 halide solid electrolyte and 0.05 g of VGCF in a mortar in a mass ratio of 65:30:5, and grind them for 20 min to obtain a composite positive electrode raw material;

[0070] (3) Weigh 120 mg of Li3YCl6 halide solid electrolyte, put it into the inner liner of a solid-state battery mold with a diameter of 12 mm and spread it evenly, then press it into a tablet at a pressure of 300-500 MPa and hold the pressure for 60 seconds;

[0071] (4) Weigh 8 mg of the composite positive electrode raw material obtained in step 2), put it into the inner liner of the solid-state battery mold on one side of the Li3YCl6 halide solid electrolyte and spread it evenly, then compact the composite positive electrode raw material and the Li3YCl6 electrolyte layer at a pressure of 300 to 500 MPa, and maintain the pressure for 60 seconds;

[0072] (5) A lithium-indium alloy with a diameter of 10 mm and a thickness of 0.2 mm is attached to the other side of the Li3YCl6 solid electrolyte, and then compacted at a pressure of 300 to 500 MPa;

[0073] (6) Finally, the solid-state battery mold liner is placed into the solid-state battery mold, and the screws are tightened at a pressure of 30 MPa for packaging to obtain a lithium-rich manganese-based all-solid-state battery.

[0074] (7) Figure 3 As shown, the first cycle charge and discharge test of the all-solid-state battery was carried out at 60°C and 0.1C. The lithium-rich manganese-based positive electrode material coated with single-element tellurium had a significant improvement in the first cycle discharge capacity and coulombic efficiency.

[0075] Embodiment 4:

[0076] A lithium-rich manganese-based positive electrode material containing a coating layer and application thereof in an all-solid-state lithium battery, comprising the following steps:

[0077] (1) First, weigh 1g of lithium-rich manganese-based positive electrode material (Li 1.2 Mn 0.54 Co 0.13 Ni 0.13 O2), 0.04 g of elemental iodine (I) was placed in anhydrous ethanol, ultrasonically dispersed for 30 min, transferred to a glove box under an inert atmosphere, and heated to remove the ethanol to obtain a lithium-rich manganese-based positive electrode material coated with elemental iodine;

[0078] (2) Weigh 0.65 g of the lithium-rich manganese-based positive electrode particles coated with elemental iodine (I) obtained in step 1), 0.30 g of Li3InCl6 halide solid electrolyte and 0.05 g of VGCF in a mortar in a mass ratio of 65:30:5, and grind them for 20 min to obtain a composite positive electrode raw material;

[0079] (3) Weigh 80 mg of Li3InCl6 halide solid electrolyte, put it into the inner tank of a solid-state battery mold with a diameter of 12 mm and spread it evenly, and then press it into a tablet at a pressure of 300-500 MPa; continue to weigh 50 mg of Li6PS5Cl sulfide solid electrolyte, put it into the solid-state battery mold where the Li3InCl6 halide solid electrolyte sheet already exists and spread it evenly, and then press it into a double-layer heterogeneous electrolyte layer with the halide solid electrolyte layer at a pressure of 300-500 MPa, and maintain the pressure for 60 seconds;

[0080] (4) Weigh 8 mg of the composite positive electrode raw material obtained in step 2), put it into the inner tank of the solid-state battery mold on one side of the Li3InCl6 halide solid electrolyte and spread it evenly, then compact the composite positive electrode raw material and the double-layer electrolyte layer at a pressure of 300 to 500 MPa, and maintain the pressure for 60 seconds;

[0081] (5) A lithium-indium alloy with a diameter of 10 mm and a thickness of 0.2 mm is placed on one side of the Li6PS5Cl sulfide solid electrolyte and then compacted at a pressure of 10 MPa;

[0082] (6) Finally, the solid-state battery mold liner is placed into the solid-state battery mold, and the screws are tightened at a pressure of 30 MPa for packaging to obtain a lithium-rich manganese-based all-solid-state battery;

[0083] (7) Figure 4 As shown, the all-solid-state battery was subjected to a long cycle charge and discharge test at 60°C and 0.5C. The lithium-rich manganese-based positive electrode coated with elemental iodine showed significant improvements in discharge specific capacity and cycle stability.

[0084] Embodiment 5:

[0085] A lithium-rich manganese-based positive electrode material containing a coating layer and application thereof in an all-solid-state lithium battery, comprising the following steps:

[0086] (1) Coating the lithium-rich manganese-based positive electrode material by ball milling: First, weigh 1g of lithium-rich manganese-based positive electrode material (Li 1.2 Mn 0.54 Co 0.13 Ni 0.13 O2), 0.03g sodium phosphide (Na3P), sealed in a ball mill jar under an inert atmosphere, H2O <0.01ppm, O2 <0.01ppm in the inert atmosphere, then ball milled in a ball mill at a speed of 400r / min for 2h to obtain a coated lithium-rich manganese-based positive electrode material, and finally transferred to a glove box under an inert atmosphere to obtain a sodium phosphide-coated lithium-rich manganese-based positive electrode material;

[0087] (2) Weigh 0.65 g of the sodium phosphide-coated lithium-rich manganese-based positive electrode particles obtained in step 1), 0.30 g of Li3InCl6 halide solid electrolyte and 0.05 g of VGCF in a mortar in a mass ratio of 65:30:5, and grind them for 20 min to obtain a composite positive electrode raw material;

[0088] (3) Weigh 80 mg of Li3InCl6 halide solid electrolyte, put it into the inner liner of a solid-state battery mold with a diameter of 12 mm and spread it evenly, then press it into a tablet at a pressure of 300-500 MPa; continue to weigh 50 mg of Li6PS5Cl sulfide solid electrolyte, put it into the solid-state battery mold with an existing Li3InCl6 halide solid electrolyte sheet and spread it evenly, then press it into a double-layer heterogeneous electrolyte layer with a pressure of 300-500 MPa, and maintain the pressure for 60 seconds; (4) Weigh 8 mg of the composite positive electrode raw material obtained in step 2), put it into the inner liner of the solid-state battery mold on one side of the Li3InCl6 halide solid electrolyte and spread it evenly, then compact the composite positive electrode raw material and the double-layer electrolyte layer at a pressure of 300-500 MPa, and maintain the pressure for 60 seconds;

[0089] (5) A lithium sheet with a diameter of 10 mm and a thickness of 0.2 mm was attached to one side of the Li6PS5Cl sulfide solid electrolyte and then compacted at a pressure of 10 MPa;

[0090] (6) Finally, the solid-state battery mold liner is placed into the solid-state battery mold, and the screws are tightened at a pressure of 30 MPa for packaging to obtain a lithium-rich manganese-based all-solid-state battery;

[0091] (7) Figure 5 As shown, the first cycle charge and discharge test of the all-solid-state battery was carried out at 30°C and 0.1C, and the first cycle charge and discharge capacity of the sodium phosphide-coated lithium-rich manganese-based positive electrode material was significantly improved.

[0092] Embodiment 6:

[0093] A lithium-rich manganese-based positive electrode material containing a coating layer and application thereof in an all-solid-state lithium battery, comprising the following steps:

[0094] (1) Coating the lithium-rich manganese-based positive electrode material by ball milling: First, weigh 1g of lithium-rich manganese-based positive electrode material (Li 1.2 Mn 0.54 Co 0.13 Ni 0.13 O2), 0.03g potassium phosphide (K3P), sealed in a ball mill jar under an inert atmosphere, H2O <0.01ppm, O2 <0.01ppm in the inert atmosphere, then ball milled in a ball mill at a speed of 400r / min for 2h to obtain the coated lithium-rich manganese-based positive electrode material, and finally transferred to a glove box under an inert atmosphere to obtain a potassium phosphide-coated lithium-rich manganese-based positive electrode material;

[0095] (2) Weigh 0.65 g of the sodium phosphide-coated lithium-rich manganese-based positive electrode particles obtained in step 1), 0.30 g of Li3InCl6 halide solid electrolyte and 0.05 g of VGCF in a mortar in a mass ratio of 65:30:5, and grind them for 20 min to obtain a composite positive electrode raw material;

[0096] (3) Weigh 80 mg of Li3InCl6 halide solid electrolyte, put it into the inner tank of a solid-state battery mold with a diameter of 12 mm and spread it evenly, and then press it into a tablet at a pressure of 300-500 MPa; continue to weigh 50 mg of Li6PS5Cl sulfide solid electrolyte, put it into the solid-state battery mold where the Li3InCl6 halide solid electrolyte sheet already exists and spread it evenly, and then press it into a double-layer heterogeneous electrolyte layer with the halide solid electrolyte layer at a pressure of 300-500 MPa, and maintain the pressure for 60 seconds;

[0097] (4) Weigh 8 mg of the composite positive electrode raw material obtained in step 2), put it into the inner tank of the solid-state battery mold on one side of the Li3InCl6 halide solid electrolyte and spread it evenly, then compact the composite positive electrode raw material and the double-layer electrolyte layer at a pressure of 300 to 500 MPa, and maintain the pressure for 60 seconds;

[0098] (5) A lithium sheet with a diameter of 10 mm and a thickness of 0.2 mm was attached to one side of the Li6PS5Cl sulfide solid electrolyte and then compacted at a pressure of 10 MPa;

[0099] (6) Finally, the solid-state battery mold liner is placed into the solid-state battery mold, and the screws are tightened at a pressure of 30 MPa for packaging to obtain a lithium-rich manganese-based all-solid-state battery;

[0100] (7) Figure 6 As shown, the all-solid-state battery was subjected to a long cycle charge and discharge test at 30°C and 0.1C. After 100 charge and discharge tests, the median voltage retention rate of the potassium phosphide-coated lithium-rich manganese-based positive electrode was significantly improved.

[0101] Embodiment 7:

[0102] A lithium-rich manganese-based positive electrode material containing a coating layer and application thereof in an all-solid-state lithium battery, comprising the following steps:

[0103] (1) Coating the lithium-rich manganese-based positive electrode material by ball milling: First, weigh 1g of lithium-rich manganese-based positive electrode material (Li 1.2 Mn 0.54 Co 0.13 Ni 0.13O2), 0.03g sodium arsenide (Na3As), sealed in a ball mill jar under an inert atmosphere, H2O < 0.01ppm, O2 < 0.01ppm in the inert atmosphere, then ball milled in a ball mill at a speed of 400r / min for 2h to obtain a coated lithium-rich manganese-based positive electrode material, and finally transferred to a glove box under an inert atmosphere to obtain a sodium arsenide-coated lithium-rich manganese-based positive electrode material;

[0104] (2) Weigh 0.65 g of the sodium arsenide-coated lithium-rich manganese-based positive electrode particles obtained in step 1), 0.30 g of Li3InCl6 halide solid electrolyte and 0.05 g of the mixture in a mortar in a mass ratio of 65:30:5, and grind them in a mortar for 20 min to obtain a composite positive electrode raw material;

[0105] (3) Weigh 80 mg of Li3InCl6 halide solid electrolyte, put it into the inner tank of a solid-state battery mold with a diameter of 12 mm and spread it evenly, and then press it into a tablet at a pressure of 300-500 MPa; continue to weigh 50 mg of Li6PS5Cl sulfide solid electrolyte, put it into the solid-state battery mold where the Li3InCl6 halide solid electrolyte sheet already exists and spread it evenly, and then press it into a double-layer heterogeneous electrolyte layer with the halide solid electrolyte layer at a pressure of 300-500 MPa, and maintain the pressure for 60 seconds;

[0106] (4) Weigh 8 mg of the composite positive electrode raw material obtained in step 2), put it into the inner tank of the solid-state battery mold on one side of the Li3InCl6 halide solid electrolyte and spread it evenly, then compact the composite positive electrode raw material and the double-layer electrolyte layer at a pressure of 300 to 500 MPa, and maintain the pressure for 60 seconds;

[0107] (5) A lithium sheet with a diameter of 10 mm and a thickness of 0.2 mm was attached to one side of the Li6PS5Cl sulfide solid electrolyte and then compacted at a pressure of 10 MPa;

[0108] (6) Finally, the solid-state battery mold liner is placed into the solid-state battery mold, and the screws are tightened at a pressure of 30 MPa for packaging to obtain a lithium-rich manganese-based all-solid-state battery;

[0109] (7) Figure 7 As shown, the all-solid-state battery was charged and discharged at 30°C and 0.1C. After 100 charge and discharge tests, the discharge specific capacity and capacity retention rate of the sodium arsenide-coated lithium-rich manganese-based positive electrode were significantly improved.

[0110] Embodiment 8:

[0111] A lithium-rich manganese-based positive electrode material containing a coating layer and application thereof in an all-solid-state lithium battery, comprising the following steps:

[0112] (1) First, weigh 1g of lithium-rich manganese-based positive electrode material (Li 1.2 Mn 0.54 Co 0.13 Ni 0.13 O2), 0.04g lithium iodide (LiI) was put into deionized water, ultrasonically dispersed for 30min, heated at 100°C in vacuum to remove crystal water, and then transferred to a glove box under an inert atmosphere to obtain a lithium iodide-coated lithium-rich manganese-based positive electrode material;

[0113] (2) Weigh 0.65 g of the lithium iodide-coated lithium-rich manganese-based positive electrode particles obtained in step 1), 0.30 g of Li3InCl6 halide solid electrolyte and 0.05 g of VGCF in a mortar in a mass ratio of 65:30:5, and grind them for 20 min to obtain a composite positive electrode raw material;

[0114] (3) Weigh 80 mg of Li3InCl6 halide solid electrolyte, put it into the inner tank of a solid-state battery mold with a diameter of 12 mm and spread it evenly, and then press it into a tablet at a pressure of 300-500 MPa; continue to weigh 50 mg of Li6PS5Cl sulfide solid electrolyte, put it into the solid-state battery mold where the Li3InCl6 halide solid electrolyte sheet already exists and spread it evenly, and then press it into a double-layer heterogeneous electrolyte layer with the halide solid electrolyte layer at a pressure of 300-500 MPa, and maintain the pressure for 60 seconds;

[0115] (4) Weigh 8 mg of the composite positive electrode raw material obtained in step 2), put it into the inner tank of the solid-state battery mold on one side of the Li3InCl6 halide solid electrolyte and spread it evenly, then compact the composite positive electrode raw material and the double-layer electrolyte layer at a pressure of 300 to 500 MPa, and maintain the pressure for 60 seconds;

[0116] (5) A lithium-indium alloy with a diameter of 10 mm and a thickness of 0.2 mm is placed on one side of the Li6PS5Cl sulfide solid electrolyte and then compacted at a pressure of 10 MPa;

[0117] (6) Finally, the solid-state battery mold liner is placed into the solid-state battery mold, and the screws are tightened at a pressure of 30 MPa for packaging to obtain a lithium-rich manganese-based all-solid-state battery.

[0118] (7) The all-solid-state battery was charged and discharged at 30°C and 0.1C. The impedance of the battery after the first charge and discharge was as follows: Figure 8 As shown, the impedance value of the lithium-rich manganese-based solid-state battery after lithium iodide coating is smaller.

[0119] Embodiment 9:

[0120] A lithium-rich manganese-based positive electrode material containing a coating layer and application thereof in an all-solid-state lithium battery, comprising the following steps:

[0121] (1) First, weigh 1g of lithium-rich manganese-based positive electrode material (Li 1.2 Mn 0.54 Co 0.13 Ni 0.13 O2), 0.04g potassium iodide (KI) was put into deionized water, ultrasonically dispersed for 30 minutes, heated at 100°C in vacuum to remove water, and then transferred to a glove box under an inert atmosphere to obtain a lithium-rich manganese-based positive electrode material coated with potassium iodide;

[0122] (2) Weigh 0.65 g of the potassium iodide-coated lithium-rich manganese-based positive electrode particles obtained in step 1), 0.30 g of Li3InCl6 halide solid electrolyte and 0.05 g of VGCF in a mortar in a mass ratio of 65:30:5, and grind them for 20 min to obtain a composite positive electrode raw material;

[0123] (3) Weigh 80 mg of Li3InCl6 halide solid electrolyte, put it into the inner tank of a solid-state battery mold with a diameter of 12 mm and spread it evenly, and then press it into a tablet at a pressure of 300-500 MPa; continue to weigh 50 mg of Li6PS5Cl sulfide solid electrolyte, put it into the solid-state battery mold where the Li3InCl6 halide solid electrolyte sheet already exists and spread it evenly, and then press it into a double-layer heterogeneous electrolyte layer with the halide solid electrolyte layer at a pressure of 300-500 MPa, and maintain the pressure for 60 seconds;

[0124] (4) Weigh 8 mg of the composite positive electrode raw material obtained in step 2), put it into the inner tank of the solid-state battery mold on one side of the Li3InCl6 halide solid electrolyte and spread it evenly, then compact the composite positive electrode raw material and the double-layer electrolyte layer at a pressure of 300 to 500 MPa, and maintain the pressure for 60 seconds;

[0125] (5) A lithium-indium alloy with a diameter of 10 mm and a thickness of 0.2 mm is placed on one side of the Li6PS5Cl sulfide solid electrolyte and then compacted at a pressure of 10 MPa;

[0126] (6) Finally, the solid-state battery mold liner is placed into the solid-state battery mold, and the screws are tightened at a pressure of 30 MPa for packaging to obtain a lithium-rich manganese-based all-solid-state battery;

[0127] (7) The all-solid-state battery was charged and discharged at 30°C and 0.1C. The DC / DV curve during the first charge and discharge is as follows: Fig. 9 As shown, after potassium iodide coating, the Li2MnO3 phase of the lithium-rich manganese-based positive electrode material is more fully activated.

[0128] Embodiment 10:

[0129] A lithium-rich manganese-based positive electrode material containing a coating layer and application thereof in an all-solid-state lithium battery, comprising the following steps:

[0130] (1) First, weigh 1g of lithium-rich manganese-based positive electrode material (Li 1.2 Mn 0.54 Co 0.13 Ni 0.13 O2), 0.04 g of sodium iodide (NaI) was put into deionized water, ultrasonically dispersed for 30 min, heated at 130 ° C in vacuum to remove crystal water, and then transferred to a glove box under an inert atmosphere to obtain a sodium iodide-coated lithium-rich manganese-based positive electrode material;

[0131] (2) Weigh 0.65 g of the sodium iodide-coated lithium-rich manganese-based positive electrode particles obtained in step 1), 0.30 g of Li3InCl6 halide solid electrolyte and 0.05 g of VGCF in a mortar in a mass ratio of 65:30:5, and grind them for 20 min to obtain a composite positive electrode raw material;

[0132] (3) Weigh 80 mg of Li3InCl6 halide solid electrolyte, put it into the inner tank of a solid-state battery mold with a diameter of 12 mm and spread it evenly, and then press it into a tablet at a pressure of 300-500 MPa; continue to weigh 50 mg of Li6PS5Cl sulfide solid electrolyte, put it into the solid-state battery mold where the Li3InCl6 halide solid electrolyte sheet already exists and spread it evenly, and then press it into a double-layer heterogeneous electrolyte layer with the halide solid electrolyte layer at a pressure of 300-500 MPa, and maintain the pressure for 60 seconds;

[0133] (4) Weigh 8 mg of the composite positive electrode raw material obtained in step 2), put it into the inner tank of the solid-state battery mold on one side of the Li3InCl6 halide solid electrolyte and spread it evenly, then compact the composite positive electrode raw material and the double-layer electrolyte layer at a pressure of 300 to 500 MPa, and maintain the pressure for 60 seconds;

[0134] (5) A lithium-indium alloy with a diameter of 10 mm and a thickness of 0.2 mm is placed on one side of the Li6PS5Cl sulfide solid electrolyte and then compacted at a pressure of 10 MPa;

[0135] (6) Finally, the solid-state battery mold liner is placed into the solid-state battery mold, and the screws are tightened at a pressure of 30 MPa for packaging to obtain a lithium-rich manganese-based all-solid-state battery;

[0136] (7) Fig.10 As shown, the all-solid-state battery was charged and discharged at 30°C and 0.1C, and the impedance of the solid-state battery was tested after 100 cycles. The lithium-rich manganese-based solid-state battery coated with sodium iodide has a smaller impedance and fewer interface side reactions occur on the surface.

[0137] Comparative Example 1:

[0138] A lithium-rich manganese-based positive electrode material containing a coating layer and application thereof in an all-solid-state lithium battery, comprising the following steps:

[0139] (1) Weigh 0.65 g of uncoated lithium-rich manganese-based positive electrode particles (Li 1.2 Mn 0.54 Co 0.13 Ni 0.13 O2), 0.30g Li3InCl6 halide solid electrolyte and 0.05g VGCF, grind in a mortar for 20min to obtain a composite positive electrode raw material;

[0140] (2) Weigh 80 mg of Li3InCl6 halide solid electrolyte, put it into the inner tank of a solid-state battery mold with a diameter of 12 mm and spread it evenly, and then press it into a tablet at a pressure of 300 to 500 MPa; continue to weigh 50 mg of Li6PS5Cl sulfide solid electrolyte, put it into the solid-state battery mold where the Li3InCl6 halide solid electrolyte sheet already exists and spread it evenly, and then press it into a double-layer heterogeneous electrolyte layer together with the halide solid electrolyte layer at a pressure of 300 to 500 MPa;

[0141] (3) Weigh 8 mg of the composite positive electrode raw material obtained in step 2), put it into the inner tank of the solid-state battery mold on one side of the Li3InCl6 halide solid electrolyte and spread it evenly, then compact the composite positive electrode raw material and the double-layer electrolyte layer at a pressure of 300 to 500 MPa, and maintain the pressure for 60 seconds;

[0142] (4) A lithium sheet with a diameter of 10 mm and a thickness of 0.2 mm was attached to one side of the Li6PS5Cl sulfide solid electrolyte, and then compacted at a pressure of 10 MPa for 60 seconds.

[0143] (5) Finally, the solid-state battery mold liner is placed into the solid-state battery mold, and the screws are tightened at a pressure of 30 MPa for packaging to obtain a lithium-rich manganese-based all-solid-state battery;

[0144] (6) The obtained all-solid-state battery was charged and discharged at 0.1C at 30°C, with a cut-off voltage of 2.0 to 4.8V. The first cycle charge and discharge curve is as follows: Fig.11 As shown. It can be concluded that the lithium-rich manganese-based positive electrode material can exert about 65% of the specific capacity of the liquid battery in the halide solid electrolyte.

[0145] The above-described embodiments are only preferred solutions of the present invention and are not intended to limit the present invention in any form. Other variations and modifications are possible without exceeding the technical solutions described in the claims.

Claims

1. A lithium-rich manganese-based positive electrode material containing a coating layer, characterized in that: The coating material of the coating layer is selected from at least one of the elemental simple substances of P, As, Te, I and their corresponding alkali metal compounds, and the alkali metal includes at least one of Li, Na and K.

2. The lithium-rich manganese-based positive electrode material containing a coating layer according to claim 1, characterized in that: The coating layer is at least one of P, As, Te, I, Na3P, K3P, Na3As, LiI, KI, and NaI.

3. A lithium-rich manganese-based positive electrode material containing a coating layer according to claim 1 or 2, characterized in that: The chemical formula of the lithium-rich manganese-based positive electrode material is xLi2MnO3·(1-x)LiMO2; wherein M is at least one of Mn, Co, and Ni; 0≤x≤1.

4. A lithium-rich manganese-based positive electrode material containing a coating layer according to claim 1 or 2, characterized in that: The weight of the coating layer is 0.01-20% of the lithium-rich manganese-based positive electrode material containing the coating layer.

5. A lithium-rich manganese-based positive electrode material containing a coating layer according to claim 1 or 2, characterized in that: The coating method of the coating layer is selected from at least one of a liquid phase coating method, a solid phase coating method and a gas phase coating method.

6. Use of a lithium-rich manganese-based positive electrode material containing a coating layer as described in any one of claims 1 to 5 in an all-solid-state lithium battery.

7. The use of a lithium-rich manganese-based positive electrode material containing a coating layer in an all-solid-state lithium battery according to claim 6, characterized in that: The application includes an all-solid-state lithium battery, wherein the all-solid-state lithium battery includes a solid electrolyte, and the solid electrolyte includes a halide solid electrolyte.

8. The use of a lithium-rich manganese-based positive electrode material containing a coating layer in an all-solid-state lithium battery according to claim 7, characterized in that: The all-solid-state lithium battery includes a composite lithium-rich manganese positive electrode material, which is obtained by fully mixing and grinding a lithium-rich manganese-based positive electrode material containing a coating layer, a halide solid electrolyte and a conductive agent; the mass proportion of the lithium-rich manganese-based positive electrode material containing a coating layer, the halide solid electrolyte and the conductive agent is 30-90:20-45:3-7.

9. The use of a lithium-rich manganese-based positive electrode material containing a coating layer in an all-solid-state lithium battery according to claim 8, characterized in that: The solid electrolyte of the all-solid-state lithium battery includes a halide solid electrolyte layer and a sulfide solid electrolyte layer. The halide solid electrolyte layer is bonded to the composite lithium-rich manganese positive electrode material, and the sulfide solid electrolyte layer is bonded to the negative electrode material.

10. The use of a lithium-rich manganese-based positive electrode material containing a coating layer in an all-solid-state lithium battery according to claim 7, characterized in that: The method for preparing the all-solid-state lithium battery comprises the following steps: 1) fully mixing and grinding the lithium-rich manganese-based positive electrode material, the halide solid electrolyte powder and the conductive agent in a mass ratio of 30-90:20-45:3-7 to obtain a composite lithium-rich manganese positive electrode material; 2) uniformly sprinkle the halide solid electrolyte powder and the sulfide solid electrolyte powder into a tablet pressing mold in sequence, and maintain the pressure at 300 to 500 MPa for 30 to 60 seconds to press the powder electrolyte into tablets; 3) Sprinkling the composite lithium-rich manganese cathode material evenly on one side of the halide solid electrolyte, and maintaining the pressure at a pressure of 300 to 500 MPa for 60 to 120 seconds; 4) Add negative electrode material on one side of the sulfide solid electrolyte.

Citation Information

Patent Citations

  • Metal halide coatings on lithium ion battery positive electrode materials and corresponding batteries

    CN103140962A

  • Low-temperature vapor deposition coated high-nickel ternary layered positive electrode material and preparation method thereof

    CN112768662A

  • Positive electrode for lithium ion battery as well as preparation method and application of positive electrode

    CN113113586A

  • Positive electrode active material, preparation method thereof and obtained lithium ion battery

    CN115332504A

  • High-voltage all-solid-state battery positive electrode material as well as preparation method and application thereof

    CN116053438A

Cited By

  • Modified lithium-rich manganese-based positive electrode material as well as preparation method and application thereof

    CN121964604A

  • A modified lithium-rich manganese-based positive electrode material, a preparation method and application thereof

    CN121964604B